All-Frequency Rendering of Dynamic, Spatially-Varying Reï¬‚ectance - Wang, Jiaping; Gong, Minmin; Snyder, John; Guo, Baining; Ren, Peiran (ACM Transactions on Graphics, 2007)
We describe a technique for real-time rendering of dynamic, spatially-varying BRDFs in static scenes with all-frequency shadows from environmental and point lights. The 6D SVBRDF is rep- resented with a general microfacet model and spherical lobes ﬁt to its 4D spatially-varying normal distribution function (SVNDF). A sum of spherical Gaussians (SGs) provides an accurate approximation with a small number of lobes. Parametric BRDFs are ﬁt on-the-ﬂy using simple analytic expressions; measured BRDFs are ﬁt as a preprocess using nonlinear optimization. Our BRDF representation is compact, allows detailed textures, is closed under products and rotations, and supports reﬂectance of arbitrarily high specularity. At run-time, SGs representing the NDF are warped to align the half-angle vector to the lighting direction and multiplied by the microfacet shadowing and Fresnel factors. This yields the relevant 2D view slice on-the-ﬂy at each pixel, still represented in the SG basis. We account for macro-scale shadowing using a new, nonlinear visibility representation based on spherical signed distance functions (SSDFs). SSDFs allow per-pixel interpolation of high-frequency visibility without ghosting and can be multiplied by the BRDF and lighting efﬁciently on the GPU. https://youtu.be/ux-IlJkkYkA https://youtu.be/qBDpGmAOVLw https://youtu.be/aCyEKDarK8A https://youtu.be/3AD1oY775C4 https://youtu.be/3K7XPg1lDos https://youtu.be/JPn36MaySXc https://youtu.be/oSWwP03WDjw